Efektivitas Vaksinasi Crude dan Soluble Protein Spora Myxobolus Koi terhadap Tingkat Kerusakan Usus Ikan Koi (Cyprinus carpio Koi) [ The Effectivety Crude and Soluble Protein of Myxobolus Koi Spore againts Intestine Different Degrees in Koi (Cyprinus carpio Koi)] - Gunanti Mahasri; Rachma Woro Anggarani; Lucia Tri Suwanti (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Myxobolus koi is one species of Myxobolus sp that can cause parasitic diseases in fish called Myxobolusis. Based on the Decree of the Minister of Marine and Fisheries No: KEP.03/MEN/2010 that Myxobolus koi in the list of Fish Quarantine Pests group I. Myxosporean diseases are most numerous in the water can cause Proliferative Kidney Disease (PKD) and Whirling Disease (WD). The aim of this research is to finding, analyzing and determining the protein of spores Myxobolus koi that can effectively reduce the level of damage to the intestinal organs as well as for the prevention myxobolusis on Koi's. Then for finding, analyzing and determining the protein of spores Myxobolus koi do isolation of spore proteins. The study consisted of three phases examination to preparation and identification of spores, isolation and analyze of crude and soluble protein spores for obtain dose and molecular weight each protein and histopathological test. This research uses descriptive method. The data presented may be narratives, images, tables or charts for each group. Intestinal histopathology test results of research carried scoring Koi's were analyzed using the Kruskal-Wallis. The results showed a profile crude protein and soluble proteins from spores Myxobolus koi showed that the molecular weight of crude protein Myxobolus koi in this study was 150 kDa and 72 kDa and for soluble protein was 73 kDa. Results scoring the degree of infection caused by exposure to Myxobolus koi then statistically processed with an average yield of scoring in a sequence of 0; 1.6; 0.64 and 0.32. Statistical analysis showed no significant difference in the treatment of K + with crude protein, and K + with soluble proteins. Statistical analysis showed that there were significant differences in treatment with K+ and K-, K- with soluble protein and crude protein and soluble protein. Histopathological changes in the intestine in the form of inflammatory cell infiltration, necrosis and haemorage